Peningkatan Kreatifitas dan Inovasi Pamong Desa melalui Pelatihan Digitalisasi File Arsip Desa - Rr Chusnu Syarifa Diah Kusuma; Mochamad Hanafi; Suhartanto Suhartanto (Penerbit Goodwood, 2023)
Purpose: This activity aims to provide training to village officials in digitizing village archive files at the Ketawang Village office, Kec. Grabbag, Kab. Magelang, Prov. Central Java. Research Methodology: The community service team chose activity methods including discussions to provide knowledge and understanding, training to provide technical skills, and evaluation for supervision and assessment to village officials in digitizing village archive files at the village office. Results: The implementation of the service begins with the coordination of the service team to determine the location and time of service. For the first day, it was conducted for the presentation of materials related to the digitization of village archives. On the second day, the practice of managing electronic archives was carried out starting from digitizing documents and storing them digitally. Village officials have improved understanding of differences, manual and electronic archives, knowledge of electronic archives, life cycle of electronic archives, creation of electronic filing systems, practice of making electronic filing systems. Conclusions: Service activities have been carried out well and smoothly so as to provide benefits for village officials. Participants have the understanding and skills related to digital archiving. This training is very useful to help the participants' work in service efforts to the community. Limitations: Activities are limited to only 30 participants. Contribution: Activities related to digitizing village archive files at the Ketawang Village office, Kec. Grabbag, Kab. Magelang, Prov. Central Java.